Dynamics of Corporate Financial Performance in IDX Carbon Initial Trading Participation: A DuPont Five-Step Approach - Danil Maulana; A. Ifayani Haanurat; Asri Jaya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Global warming and increasing greenhouse gas emissions are driving various countries to develop carbon trading mechanisms as an instrument for emission control, including in Indonesia through the launch of IDX Carbon on September 26, 2023. This research aims to examine the dynamics of companies' financial performance before, during, and after participation in the inaugural carbon trading transaction via IDX Carbon using the DuPont Five-Step Analysis approach. The research population includes 16 companies participating in the inaugural IDX Carbon transaction, with a sample of seven companies selected using purposive sampling based on the availability of financial statements and annual reports. The data used consists of quarterly financial statements for the 2022-2024 period. The research problem focuses on the differences in Return On Equity (ROE) before, during, and after participation, as well as changes in DuPont components and their correlation to ROE. The analysis methods include descriptive analysis, comparative analysis, and correlation testing of DuPont components consisting of tax burden, interest burden, operating profit margin, asset turnover, and financial leverage. The research results indicate that companies' participation in the inaugural IDX Carbon transaction was not followed by a significant change in ROE in the short term. However, there were adjustments in the ROE-forming structure, especially an increase in interest burden pressure and the important role of operational efficiency and asset utilization in maintaining profitability. This research concludes that the impact of carbon trading on companies' financial performance is transitional and is more reflected through the dynamics of DuPont components than through aggregate changes in ROE.